The Urgency of Using Electronic Evidence in Trials as an Effort to Answer the Challenges of Law Enforcement in the Digital Era and Social Media Dynamics - Sujatmiko, Bambang; Soesatyo, Bambang (Pelopor Publikasi Akademika, 2025)
The rapid advancement of information technology has transformed many aspects of legal proceedings, particularly in the area of evidence. One of the most urgent adaptations is the use of electronic evidence in court trials, especially in response to the increasing influence of social media on legal processes and public perception. This article examines the urgency of integrating electronic evidence in judicial practice in Indonesia, exploring both its legal basis and implementation challenges. Drawing on a normative legal method, the study analyzes key regulations such as the ITE Law, PERMA No. 1 of 2019, and relevant jurisprudence. The findings reveal that while electronic evidence is legally recognized, its effective application is hindered by the absence of clear procedural norms in the Criminal Procedure Code, inconsistent judicial interpretations, and the lack of technical capacity among law enforcement officers. Challenges also arise in authenticating complex digital evidence and ensuring cybersecurity within the e-court system. Despite these obstacles, the study highlights that electronic evidence significantly contributes to transparency, efficiency, and the integrity of modern trials. To optimize its use, reforms are needed in both regulatory frameworks and institutional readiness. This includes revising the Criminal Procedure Code, enhancing digital forensic training, and securing digital infrastructures. Ultimately, the use of electronic evidence is not only a technical necessity but also a strategic instrument for ensuring justice in an increasingly digital society.